Handbook of Nonlocal Continuum Mechanics for Materials and Structures - Voyiadjis, George Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This handbook covers all areas of nonlocal continuum mechanics including theoretical aspects,computational procedures, and experimental advances. The multidisciplinary scope of articles that comprise this reference are written by internationally recognized experts in the field and stand as the most-up-to-date, established knowledge base on using nonlocal continuum mechanics to characterize material behavior for advanced composites and nano-materials, as well as for engineering scale structures. The handbook is at once a comprehensive reference for academic researchers and engineers in industry concerned with nonlocal continuum mechanics for materials and structures as well as a supplement for graduate courses on a range of topics.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Nanotechnology; Materials; Engineering mathematics; Engineering -- Data processing; Solid Mechanics; Characterization and Analytical Technique; Nanotechnology; Materials Engineering; Mathematical and Computational Engineering Applications